2015
DOI: 10.1042/cs20140688
|View full text |Cite
|
Sign up to set email alerts
|

Placental DNA methylation of peroxisome-proliferator-activated receptor-γ co-activator-1α promoter is associated with maternal gestational glucose level

Abstract: Intrauterine exposure to hyperglycaemia may increase the risk of later-life metabolic disorders. Although the underlying mechanism is not fully understood, epigenetic dysregulation in fetal programming has been implicated. With regard to energy homoeostasis, PGC-1α (peroxisome-proliferator-activated receptor γ co-activator-1α, encoded by the PPARGC1A gene) plays a regulatory role in several biochemical processes. We hypothesized that maternal gestational glucose levels would positively correlate with DNA methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 54 publications
3
29
1
Order By: Relevance
“…A portion of plasma and serum were frozen and stored at -80°C immediately after the centrifugation. Placenta tissue from the fetal side were obtained as previously described [ 31 ]. The samples were rinsed in normal saline at 4°C to remove excess maternal blood.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A portion of plasma and serum were frozen and stored at -80°C immediately after the centrifugation. Placenta tissue from the fetal side were obtained as previously described [ 31 ]. The samples were rinsed in normal saline at 4°C to remove excess maternal blood.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the patients in this report were from previously reported cohorts [ 31 ]. All study procedures were approved by the Ethic Committee of Tongji Hospital, Huazhong University of Science and Technology (Approval number: TJ-C20130711), and written informed consent was obtained from each participant in accordance with the Declaration of Helsinki as revised in 2008.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have studied the methylation pattern of this gene and showed a positive association between fetal DNA methylation and maternal glucose levels (54,56). In addition, adult offspring of GDM mothers had about 40% lower gene expression of PPARGC1A mRNA in skeletal muscle compared to that in controls (77).…”
Section: Discussionmentioning
confidence: 99%
“…A candidate gene study in placentas of 58 pregnancies with uncomplicated Cesarean delivery (56) showed that maternal glucose levels were positively associated with fetal-placental DNA methylation of PPARGC1A gene. Another study of 85 Chinese women with Cesarean R259 Review G-H Moen and others Epigenetics and gestational diabetes www.eje-online.org delivery, from a different group (57), explored the differences in placental methylation in GDM patients and preeclampsia patients compared to that in controls.…”
Section: Other Genesmentioning
confidence: 99%
See 1 more Smart Citation